Analyzing Expressive Speech Acts in The Late Late Show with James Corden - Nazrah; Rosida, Ana (Institut Agama Islam Negeri Parepare, 2024)
The Late Late program with James Corden, a prominent late-night talk program, is a great resource for studying expressive speech acts. This study aims to analyze the types of expressive speech acts performed by James Corden in The Late Late Show with James Corden. In this study, the researchers used a qualitative descriptive research method using the Searle and vanderveken (1985) theory to analyze a total of 32 utterances from the last episode of the show, which are included in the types of expressive speech acts, such as 1 data of Apologize, 4 data of Thank, 1 data of Condole, 3 data of Complain, 4 data of Lament, 5 data of Protest, 1 data of Deplore, 1 data of Boast, 5 data of Compliment, 4 data of Welcome and 3 data of Greet. The results show that, James Corden uses various expressive speech acts to interact with the audience and guests, so as to create a lively and fun atmosphere. The findings contribute to the understanding of expressive speech acts in the context of talk shows and show the importance of language in shaping social interactions and relationships.